The ecological, economic and social profile of boat based recreational fisheries of Port Dickson - Nagaraj, Gopinath (2022)
This thesis examines the social, economic and environment aspects of boat based recreational fishery in the marine district of Port Dickson, Negeri Sembilan, Malaysia. It identifies the primary fishing techniques used and species and volumes harvested and compared with the artisanal fishermen who also fished in the same waters. The Port Dickson District’s waters supported an important recreational fisheries industry, with 30 landing points utilised for that purpose. Anglers fished from boats rented from fishermen and commercial boat operators, kelong (privately owned fishing platforms), purpose built public jetties and breakwaters. Data was collected at these recreational fishing landing points indicated that activity was dominated by shore angling and boat angling. A wide range of species were caught include some such as the cobia (Rachycentron canadum) that did not appear in official fisheries statistics. The main bait types that were used included live prawn, squid, small fish and pumpum (polychete worms) as bait. The use of artificial bait or lures was almost non-existent. The paper describes a method for estimating the value of recreational fishery in Port Dickson based on fishing effort derived from interviews and discussions with recreational fishes. The investigation indicated that boat fishing in Port Dickson involved 10,066 anglers with a total fishing effort of 23,048 person-day with expenditures that amounted to RM1,490,062. Annualised catch volume, the total boat-based recreational fisheries catch is estimated to have amounted to 592 tonnes, which is not far from 2018 artisanal fisheries catch of 670 tonnes. In many landing points, recreational fisheries was found to be a major contributor to the local economy. The relationship of existing recreational fishing patterns in relation to the Port Dickson District’s natural capital was explored and discussed, especially in relation to the ability of the fishers to identified hitherto unknown habitats. The uptake by boat based recreational fisheries undermines the assumptions on which existing fisheries management regimes, which is based entirely on artisanal fishing catch, is also discussed.